2020
DOI: 10.1097/sla.0000000000004093
|View full text |Cite
|
Sign up to set email alerts
|

Detection, Treatment, and Survival of Pancreatic Cancer Recurrence in the Netherlands

Abstract: Objective: To evaluate whether detection of recurrent pancreatic ductal adenocarcinoma (PDAC) in an early, asymptomatic stage increases the number of patients receiving additional treatment, subsequently improving survival. Summary of Background data: International guidelines disagree on the value of standardized postoperative surveillance for early detection and treatment of PDAC recurrence. Methods: A nationwide, observational cohort study was performed including all patients who underwent PDAC resection (20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 37 publications
1
32
0
Order By: Relevance
“…This might be attributed to the inadequacy of the oncologic preoperative treatment, which was based on chemoradiotherapy (three courses of gemcitabine, associated with radiotherapy 36 Gy). Since most patients undergoing resection will experience distant failure ( 25 , 26 ), it may be hypothesized that a more efficacious multiagent chemotherapy will offer better long-term results than chemoradiotherapy. In this context, PACT-15, a phase 2 randomized study that used multiagent chemotherapy PEXG, showed promising results in patients treated with the perioperative approach (3 months of chemotherapy before and 3 months after surgery).…”
Section: Discussionmentioning
confidence: 99%
“…This might be attributed to the inadequacy of the oncologic preoperative treatment, which was based on chemoradiotherapy (three courses of gemcitabine, associated with radiotherapy 36 Gy). Since most patients undergoing resection will experience distant failure ( 25 , 26 ), it may be hypothesized that a more efficacious multiagent chemotherapy will offer better long-term results than chemoradiotherapy. In this context, PACT-15, a phase 2 randomized study that used multiagent chemotherapy PEXG, showed promising results in patients treated with the perioperative approach (3 months of chemotherapy before and 3 months after surgery).…”
Section: Discussionmentioning
confidence: 99%
“…Among 129 events of recurrence or death, 62 (48%) occurred within 1 year of surgery [ 19 ]. Early postoperative recurrence, particularly within 1 year, generally indicates aggressive clinical features and has been associated with worse survival than recurrence after 1 year or longer [ 20 ]. Therefore, recurrence within 1 year of surgery was defined as early recurrence in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Pancreatic cancer is one of the most aggressive cancer types, with a median overall survival rate of typically around 19 months. For non-metastatic unresectable tumors or isolated local recurrences, prognosis is around 14–15 months [1] , [2] . Stereotactic body radiotherapy (SBRT) has been shown to be a promising therapy for these tumor types in terms of local disease control [3] , [4] , [5] , [6] .…”
Section: Introductionmentioning
confidence: 99%